A monastery door from Warffum (Bulletin KNOB, 2007)
Sometime in the early 20th century the Groninger Museum acquired a primitively constructed door of an early date and presumably from Warffum. Recent research of the door revealed the identity of the building concerned, notably the ‘Johannietenklooster’ (monastery of the knights of St John) in the aforesaid village. The door is circular-arched and composed of two wide, thick oak parts and connected by means of two forged tail hinges.With the passage of time the inside was completely clamped with pinewood parts. This fact could have been marked by the date 1586 and some other signs carved in the wood. A heart-shaped shield in which the Maltese cross, the emblem of the monastic order of the knights of St John, has been carved twice, dates back to the original period. The door probably dates from the early 16th century.